In Situ Monitored Vortex Fluidic-Mediated Protein Refolding/Unfolding Using an Aggregation-Induced Emission Bioprobe - Hu, Qi (Molecules, 2021)
Protein folding is important for protein homeostasis/proteostasis in the human body. We have established the ability to manipulate protein unfolding/refolding for β-lactoglobulin using the induced mechanical energy in the thin film microfluidic vortex fluidic device (VFD) with monitoring as such using an aggregation-induced emission luminogen (AIEgen), TPE-MI. When denaturant (guanidine hydrochloride) is present with β-lactoglobulin, the VFD accelerates the denaturation reaction in a controlled way. Conversely, rapid renaturation of the unfolded protein occurs in the VFD in the absence of the denaturant. The novel TPE-MI reacts with exposed cysteine thiol when the protein unfolds, as established with an increase in fluorescence intensity. TPE-MI provides an easy and accurate way to monitor the protein folding, with comparable results established using conventional circular dichroism. The controlled VFD-mediated protein folding coupled with in situ bioprobe AIEgen monitoring is a viable methodology for studying the denaturing of proteins.